2017
DOI: 10.1002/ange.201610957
|View full text |Cite
|
Sign up to set email alerts
|

A PDE6δ‐KRas Inhibitor Chemotype with up to Seven H‐Bonds and Picomolar Affinity that Prevents Efficient Inhibitor Release by Arl2

Abstract: Small-molecule inhibition of the interaction between the KRas oncoprotein and the chaperone PDE6d impairs KRas spatial organization and signaling in cells.H owever, despite potent binding in vitro (K D < 10 nm), interference with Ras signaling and growth inhibition require 5-20 mm compound concentrations.W edemonstrate that these findings can be explained by fast release of high-affinity inhibitors from PDE6d by the release factor Arl2. This limitation is overcome by novel highly selective inhibitors that bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…2a ). We also directly monitored the effect of Deltarasin on the interaction between Rheb and PDEδ by fluorescence lifetime imaging microscopy of Förster resonance energy transfer (FLIM-FRET), with mCitrine-Rheb as the donor and PDEδ, C-terminally tagged with mCherry (mCherry-PDEδ) as FRET acceptor (29, 32, 33) ( Fig. 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…2a ). We also directly monitored the effect of Deltarasin on the interaction between Rheb and PDEδ by fluorescence lifetime imaging microscopy of Förster resonance energy transfer (FLIM-FRET), with mCitrine-Rheb as the donor and PDEδ, C-terminally tagged with mCherry (mCherry-PDEδ) as FRET acceptor (29, 32, 33) ( Fig. 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have solved structures of human farnesylated-methylated KRAS4b in complex with PDEδ in two different crystal forms. 30,31 Zimmermann and colleagues have reported that a small molecule inhibitor (deltarasin) binds to the prenyl binding pocket of PDEδ and thereby inhibits the KRAS-PDEδ interaction, which impairs KRAS signaling pathway and reduces the proliferation of human pancreatic ductal adenocarcinoma cells in vitro and in vivo. 32 However, subsequent detailed analysis of the characteristic doseresponse curves of deltarasin reveals that this PDEδ ligand displays a 'switch-like' inhibition of proliferation exhibiting cytotoxic effects at concentrations above 9 μM in all tested cell lines, including cancer and normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Small-molecule inhibitors that potently target the PDEd prenyl-binding site, for example, deltasonamide 1 (Figure 1), have proven invaluable for the study of PDEd function. [6][7][8][9] However, their application is limited by an allosteric interaction of PDEd with the Arl2/3 GTPases, which results in release of even high-affinity cargo. [4,8,9] An alternative approach to inhibition consists of eventdriven pharmacology, for example, small-molecule-induced protein degradation.…”
mentioning
confidence: 99%
“…[6][7][8][9] However, their application is limited by an allosteric interaction of PDEd with the Arl2/3 GTPases, which results in release of even high-affinity cargo. [4,8,9] An alternative approach to inhibition consists of eventdriven pharmacology, for example, small-molecule-induced protein degradation. For this purpose, heterobifunctional molecules are employed that bind the protein of interest and recruit an E3 ubiquitin ligase, followed by ubiquitination and subsequent degradation of the targeted protein.…”
mentioning
confidence: 99%
See 1 more Smart Citation